U-involved sphere-dispersed metallic glass matrix composites. (5th November 2018) - Huang, Huogen; Ke, Haibo; Zhang, Pei; Pu, Zhen; Zou, Dongli; Zhang, Pengguo; Shi, Tao; Zhang, Lei; Liu, Tianwei
Abstract: The preparation of bulk U-based metallic glasses has fails for a long time due to weak glass forming ability and the low chemical purity of raw uranium metal. To make bulk glassy samples containing uranium, the compositing approach is adopted in this study. U-involved sphere-dispersed metallic glass matrix composites are successfully in-situ synthesized with suction-casting and tilt-casting by the phase separation alloying of uranium and Zr41.2 Ti13.8 Ni10.0 Cu12.5 Be22.5 (Vit-1). These composites are in a large composition range of 3–40 at.% U and with a flexible diameter dimension of not <15 mm. The dispersing phase is α-U solid solution while the matrix is Zr-based. A typical U30.03 Zr28.83 Ti9.66 Ni7.00 Cu8.75 Be15.73 composite exhibits a compressive fracture strength of 1.7 GPa and high corrosion resistance in neutral and alkaline media. Its matrix phase shows higher thermostability and nominal glass forming ability than Vit-1 glass. This work suggests strong application potential of U-bearing glassy materials in nuclear-related fields, and also gives guidance for the development of more advanced uranium alloys. Graphical abstract: Unlabelled Image Highlights: U-involved bulk metallic glass matrix composites are produced by phase separation. The size of the U-involved glassy composites can be not less than 15 mm in diameter. A U-based composite achieves compressive strength of 1.7 Ga and acceptable anti-corrosion. The thermal stability of the glassy matrix is stronger than the mother glass.